2011
DOI: 10.1016/j.ajpath.2011.08.041
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Nitration of Prostacyclin Synthase Is Associated with Enhanced Retinal Cell Apoptosis in Diabetes

Abstract: The risk of diabetic retinopathy is associated with the presence of both oxidative stress and toxic eicosanoids. Whether oxidative stress actually causes diabetic retinopathy via the generation of toxic eicosanoids, however, remains unknown. The aim of the present study was to determine whether tyrosine nitration of prostacyclin synthase (PGIS) contributes to retinal cell death in vitro and in vivo. Exposure of human retinal pericytes to heavily oxidized and glycated LDL (HOG-LDL), but not native forms of LDL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 40 publications
3
21
0
Order By: Relevance
“…These protective effects were associated with significant decreases in lipid peroxidation and tyrosine nitration in the diabetic retina. These results are consistent with a recent report showing that administration of tempol prevented retinal tyrosine nitration and pericyte cell death and preserved BRB in Akita diabetic mice [31]. The latter study did not examine the direct effects of superoxide anion production within endothelial cells.…”
Section: Discussionsupporting
confidence: 92%
“…These protective effects were associated with significant decreases in lipid peroxidation and tyrosine nitration in the diabetic retina. These results are consistent with a recent report showing that administration of tempol prevented retinal tyrosine nitration and pericyte cell death and preserved BRB in Akita diabetic mice [31]. The latter study did not examine the direct effects of superoxide anion production within endothelial cells.…”
Section: Discussionsupporting
confidence: 92%
“…Nitrated proteins play an important role in mediating cell death responses, and their signaling has been effectively targeted to inhibit cell death in several experimental models [42], [43], [44]. However, the nitrative stress mechanism underlying cisplatin-induced ototoxicity remains only partially understood.…”
Section: Discussionmentioning
confidence: 99%
“…10 Further studies revealed that upregulation of receptors for advanced glycation end-products (AGEs) causes proinflammatory responses in Müller cells. 11 In previous work, we proposed that in addition to hyperglycemia, extravasation of plasma lipoproteins through leaking blood retinal barriers (BRB) and their subsequent modification (glycation, oxidation) are important in the propagation of DR. [12][13][14][15][16][17][18] Several lines of evidence support this concept. Clinical studies indicate that dyslipidemia is associated with the severity of DR In particular, DR is positively associated with serum levels of LDL, apolipoprotein B (ApoB), and LDL particle concentration in type 1 diabetic patients.…”
mentioning
confidence: 85%
“…Previous studies from our own and other laboratories have shown that, in addition to hyperglycemia, qualitative and quantitative lipoprotein abnormalities are implicated in mediating vascular injury in diabetes, and specifically, are associated with the development of DR. [13][14][15][16][17][18][19][20][21] Our previous studies indicated that modified (oxidized and glycated) LDL induced apoptosis in human retinal capillary pericytes in vitro. 12,14,17 In addition, large quantities of extravasated apoB100 and oxidized LDL were identified in retinal tissues from diabetic human retinas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation